(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2023)
In the stage process, unlike architectural building, the perspective method represents the creative starting point of the design process. In fact, the perspective, supporting the privileged point of view of the recipient of the fruition, expresses at the same time both the author’s design idea, and the technical information to allow its three-dimensional realization. In particular, in the stage process (a priori) and stagecraft procedure (a posteriori), the perspective instrument is concretized in the bozzetto, where it assumes a leading role in the planning process and its prefigurative value merges with the communicative hand-drawing immediacy. In such a manual skill, not only the handcraft value of the stage sketch can be retrieved, but also its artistic one, as the graphic sign does not convey only ‘objective’ data, such as the dimensioning of the stage space or its functional equipment, but also (and above all) a magisterium, unique although repeatable, which is evocative of an idea, precisely because of its autograph, thus interpretable even philologically. For this reasons, on the one hand, the sketch can be assumed as a ‘sign’, a container of information, preparatory to its three-dimensional development. On the other hand, the manual skill of its creator can be interpreted as a ‘gesture’ and therefore acquires an artistic value that cannot be darkened. If the first aspect is completed by the physical building, the second one finds its fulfilment in the performative staging. A further consideration therefore concerns the relationship between graphic expression and functionalism, whose intent, by its nature, the sketch is only apparently devoid. Through the state of the art and many examples from the classical and contemporary repertoire, the paper aims to focus on the importance of graphic-manual freedom, thanks to which the sketch activates and catalyzes imaginary, preparing them for concrete realization, without ever abandoning its constitutive manual graphic skill.